Extremely large linear magnetoresistance in antimony crystal. (25th February 2021) - Dasoundhi, Mukesh Kumar; Rajput, Indu; Kumar, Devendra; Lakhani, Archana
Abstract: In this article, we report the observation of extremely large non-saturating linear magnetoresistance (MR) in antimony (Sb) crystal. An extremely large magnetoresistance of 43 000% at 2 K and large unsaturating MR ∼70% at room temperature is observed at the magnetic field of 9 T. Hall measurements reveal a very high mobility ∼3.8 × 10 4 cm 2 V s −1 of charge carriers and strong temperature dependence of carrier concentration and mobility. The respective scaling of MR and crossover field ( B c ) from quadratic to linear MR with mobility and inverse of mobility describes the classical origin of large linear MR in this crystal as suggested by Parish and Littlewood model for disordered systems.